Dietary pattern and nutritional assessment in a cohort of mothers identified by neonatal screening for cobalamin deficiency in offspring: an Italian single center experience - Tosi, Martina; Tagi, Veronica Maria; Colombo, Alice; Cecchini, Alessandra; Zobele, Marianna; Montanari, Chiara; Ferraro, Simona; Bosetti, Alessandra; Bonaventura, Eleonora; Bruschi, Fabio; De Zan, Diego; Fiore, Giulia; et al. (Frontiers in Nutrition, 2025)
During pregnancy, nutrient requirements increase while deficiencies can significantly affect pregnancy outcomes. Deficiencies may result from inadequate dietary intake, impaired absorption, or restrictive diets. This study aimed to retrospectively assess the nutritional status and dietary intakes in a cohort of mothers whose newborns were identified with vitamin B12 deficiency of maternal origin through Newborn Screening. Between 2021 and 2024, 107 newborn-mother dyads with altered biomarkers of cobalamin metabolism were identified and referred to the Metabolic Disease Unit for further evaluation and treatment. Mothers underwent biochemical assessments and nutritional interviews regarding pregnancy diet history, and dietary intakes were quantified using a dedicated software (MetadietaVR). Most of the cohort (47%) was from Asia, with an average age of 32.5 years. Plasma vitamin B12 levels averaged 240 pg/ml. Mothers who reported taking vitamin B12 supplements had higher plasma levels compared to those who did not supplement with B12 (255.5 ± 113 vs. 231.2 ± 104 pg/ml). Dietary habits during pregnancy revealed that 71% of mothers were omnivorous (O), 16% followed a lacto-vegetarian (LV) diet, 12% a lacto-ovo-vegetarian (LOV) diet, and 1% a vegan (V) diet. Most mothers (90%) were taking supplements during pregnancy, with 70.7% taking folic acid, 68.7% iron and 15% vitamin B12. Among women who achieved adequate vitamin B12 intake through both diet and supplementation, 95% were omnivores while 5% followed a LOV diet. This study emphasizes the importance of addressing maternal nutritional needs from the pre-conception period, as dietary patterns may not adequately reflect micronutrient intake. Even omnivorous diets, if unbalanced, can result in insufficient nutrient intake, underlying the necessity of targeted nutritional support during pregnancy.